Experimental Analysis of Helix Aspersa Shell as Cementitious Material - Brescia-Noranmbuena, L (Springer Science and Business Media Deutschland GmbH, 2024)
The high environmental impact of the cement industry demands the study of new cementitious materials. Often supplementary cementitious materials such as fly ash or silica fume are used; however, the depletion of raw materials encourages the assessment of new sources. Due to the high calcium content of snail shells, this research explored the use of crushed powder of Helix Aspersa to replace cement, evaluating its use at different percentages of replacement in weight (0, 5, and 10%), calcination temperature (0, 450, and 900 °C) and water-cementitious materials ratios (0.35, 0.40, and 0.45). The results included analysing setting time, compressive and flexural strength, water absorption, and shrinkage. Results indicated that snail shells (i) create an expansion during the first days (~15%), reaching similar values at 28 days, (ii) decrease the water absorption at calcination temperatures ≥450 °C, and (iii) slightly reduce the flexural strength (~16% in average) and compressive strength (~10% in average). As the main decrement of the responses is at a low w/cm ratio, it is expected that calcined snail shells offer the opportunity to save cement and pollution from the construction industry. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.